Implementation Of Public Moral Values Based On Pancasila As The Strenght Of The Nation Rising From The Covid-19 Pandemic Period - Arief Firdaus (Al-Makki Publisher, 2022)
An abstract must accompany each manuscript; This abstract must be completely consistent on its own (eg, without numbers, tables, equations or reference citation), not exceeding 250 words and written as a paragraph. The abstract should include research background, objectives, methodology, and findings. The national identity and character of the Indonesian nation is none other than Pancasila which reflects certain concepts, principles and values contained in it. The character of the Indonesian nation also means the spiritual self of the Indonesian nation which is reflected in the mindset, attitude and pattern of action that characterizes the citizens of the Indonesian nation. In Pancasila, public moral values are reflected in the concept of Jonathan David Haidt, an American social psychologist, containing the principles of Care (Second Precept), Fairness (Fifth Precept), Liberty (Fifth Precept), Loyalty (Third Precept), Authority (Fifth Precept), Fourth Precept), Sanctity (First Precept). The implementation of public moral values originating from Pancasila can be seen in the lives of our people when facing the Covid-19 pandemic. This is what prompted the author to examine this problem with the formulation of the problem, can the implementation of public moral values derived from Pancasila give strength to the Indonesian nation to rise from the Covid-19 pandemic? By using a literacy study approach, this study concludes that the implementation of public moral values originating from Pancasila can provide strength for the Indonesian people to face and rise from the Covid-19 pandemic.